Taxation Windfall Internationalization Korean Capital Markets. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
The paper describes the evolution of the corporate stock and bond markets in Korea and the Government's role in this evolution and its policy with regard to internationalization of the capital market. The paper analyzes problems encountered in gradually opening the Korean capital market to foreign participation and suggests alternative methods of taxing the windfall that will be generated. It also discusses the desirability of taxing the capital gains on financial assets as part of the global income tax in Korea.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet